PERANCANGAN SISTEM DINAMIS BELT CONVEYOR PENGANGKUT BIJIH NIKEL KAPASITAS SEKITAR 720 TON PER JAM - Haris Rifky Setiawan (2022)
The high demand and consumer demand for using ferronickel has prompted the company to conduct large-scale expansions to increase its production capacity and quality. It is necessary to modify the carrying capacity of the nickel ore conveyor belt conveyor with an initial capacity of 400 tons to 720 tons per hour. Therefore, adesign was carried out on the dynamic system of the belt conveyor. By applying calculations to each required variable and analyzing using the finite element analysis method, this study resulted in a design for a belt conveyor system which includes belts, pulleys, and idlers. With a belt that is 36 in wide, Belt width: 36 in; belt weight 6.9 lb/ft; effective tensile force on the belt 11439.35 lbs; force on the tight side 1573.05 lbs; force on slack side 13212.4 lbs. The resulting pulley has a drive pulley diameter of 508 mm; tail pulley diameter: 508 mm; snub tail pulley diameter: 267 mm; snub head pulley diameter: 318 mm; The pulley rotation speed is 117.7 rpm. The resulting idler is a 4 in diameter roller; 4.5 ft spacing between carrying idlers; 10 ft spacing between return idlers; the load on the carrying idler is226.05 lbs; the load on the return idler is 69 lbs; idler roller rotation speed: 470.1 rpm. A power of 127.2 kW is required to drive the drive unit on the head pulley. The selection of the reduction gear is selected with a power of 22 kW and a ratio of 25. Keywords: Design, Dynamic System, Belt Conveyor